THE DEVELOPMENT OF THE PORTFOLIO MANAGEMENT FOR THE UNIT INVESTMENT FUNDS - Sergeeva, Irina; Nikiforova, Vera (Journal of Advanced Studies in Finance, 2012)
The paper analyses the common Russian assessment practice regarding the effectiveness of the unit investment fund portfolio management based on the risk/return tradeoff. In the authors’ opinion, the assessment technique should not be only quantitative, but it should also reveal the risks hidden in the implemented strategy. This approach seems to be especially important in the context of the analysis of UIFs’ performance over the last several years. Identifying funds which implemented risky strategies during the pre-crisis years could help to avoid great losses at the beginning of the world’s financial crisis. The current paper identifies characteristics, advantages and disadvantages of various portfolio risk measures and introduces the approach to risk assessment based on the analytical coefficient calculations.